2015
DOI: 10.1038/srep13135
|View full text |Cite
|
Sign up to set email alerts
|

Unique Toll-Like Receptor 4 Activation by NAMPT/PBEF Induces NFκB Signaling and Inflammatory Lung Injury

Abstract: Ventilator-induced inflammatory lung injury (VILI) is mechanistically linked to increased NAMPT transcription and circulating levels of nicotinamide phosphoribosyl-transferase (NAMPT/PBEF). Although VILI severity is attenuated by reduced NAMPT/PBEF bioavailability, the precise contribution of NAMPT/PBEF and excessive mechanical stress to VILI pathobiology is unknown. We now report that NAMPT/PBEF induces lung NFκB transcriptional activities and inflammatory injury via direct ligation of Toll–like receptor 4 (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
166
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 144 publications
(176 citation statements)
references
References 58 publications
8
166
0
2
Order By: Relevance
“…Interestingly, the expression of TLR4 and nicotinamide phosphoribosyl‐transferase ( Nampt ), an adipokine ligand that binds and activates TLR4, was reduced in HFD‐treated DAP12 KO mice compared with HFD‐treated WT mice (Fig. D ) . The expression of genes involved in fatty acid metabolism ( Alox5, Lta4H, Cd36, Acls4, Rpsbkb1, and Mtor ) was also suppressed in DAP12 KO mice compared with TLR4 KO mice (Table ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, the expression of TLR4 and nicotinamide phosphoribosyl‐transferase ( Nampt ), an adipokine ligand that binds and activates TLR4, was reduced in HFD‐treated DAP12 KO mice compared with HFD‐treated WT mice (Fig. D ) . The expression of genes involved in fatty acid metabolism ( Alox5, Lta4H, Cd36, Acls4, Rpsbkb1, and Mtor ) was also suppressed in DAP12 KO mice compared with TLR4 KO mice (Table ).…”
Section: Resultsmentioning
confidence: 96%
“…8D). (26) The expression of genes involved in fatty acid metabolism (Alox5, Lta4H, Cd36, Acls4, Rpsbkb1, and Mtor) was also suppressed in DAP12 KO mice compared with TLR4 KO mice ( Table 2). These data highlight the significant differences in IFP and synovium gene expression induced by HFD in the absence of TLR4 or DAP12.…”
Section: Hfd Decreases Ifp and Synovium Inflammation And Insulin Signmentioning
confidence: 99%
“…Interestingly, by increasing NAD levels, NAMPT promotes TNF synthesis via regulation of SIRT6 activity 29, 55 . The extracellular cytokine-like activity of NAMPT could also potentially activate NF-κB signaling and further enhance SOCE 56, 57 .…”
Section: Discussionmentioning
confidence: 99%
“…20 In our earlier published studies, we have conclusively demonstrated that secreted NAMPT binds to and activates the TLR4 receptor, and this interaction is a primary cause for the induction of proinflammatory cytokine production in mouse lungs and in human lung ECs, akin to LPS induction of TLR4. 7 Although the role of LPS in inflammatory gene transcription is well known, the mechanistic role of rhNAMPT in inflammatory cytokine induction is not completely understood. Thus, we utilized recombinant NAMPT as an agonist for TLR4 activation and demonstrated significantly decreased H3K9 acetylation in human lung ECs.…”
Section: Discussionmentioning
confidence: 99%
“…6 Additional biochemical assays exploring the activation of NFkB pathways in mouse models of VILI and human lung endothelium identified toll-like receptor 4 (TLR4) as a direct binding partner for NAMPT independent of sepsis-related stimuli via NAMPT's unique similarities to MD-2 protein sequence. 7 Although our earlier studies have also elucidated specific transcription factors that bind and augment NAMPT promoter, no studies to date have evaluated the epigenetic regulation of NAMPT expression with excessive mechanical stress. 8 Epigenetics has emerged as a critical novel regulator of gene transcription.…”
mentioning
confidence: 99%